Blasting vibration safety criterion for a tunnel liner structure - Jiang, Nan; Zhou, Chuanbo (Tunnelling and underground space technology, 2012)
► We establish the 3D numerical model of the real field engineering by LS-DYNA. ► We calculate PPVs and effective stresses of tunnel liner and surrounding rock. ► The PPV and tensile stress between tunnel liner and surrounding rock are different. ► The sequential characteristics of PPV and tensile stress are observed. ► The safety criterion of PPV in the project is determined to be 11cm/s. Due to the complexity of rock blasting mechanism and rock mass conditions, the safety criterion of blasting vibration velocity for adjacent tunnel is often set empirically without scientific theoretical basis. In order to analyze the influences of blasting vibration on tunnel structure, we calculated and analyzed the vibration velocities and effective stresses of tunnel liner and surrounding rock subject to blasting vibration by the finite element software LS-DYNA based on the field blasting tests of an excavation blasting project adjacent to a railway tunnel top. The sequential characteristics of vibration velocities and effective stresses in the elements at different positions of tunnel liner and surrounding rock are obtained. The differences of the peak particle velocities (PPVs) and the effective stresses between tunnel liner and surrounding rock subject to blasting vibration are observed. The relationship of dynamic stresses and PPVs of tunnel structure under the different blasting conditions is studied and modeled. According to the maximum tensile strength theory and the numerical calculation results, the blasting safety criterion of PPV is determined. The numerical simulation results have been confirmed by field blasting tests and provide a reference to specify blasting vibration criteria for other similar projects.